Isolation and characterization of two satellite DNAs in Atlantolacerta andreanskyi (Werner, 1929) (Reptilia, Lacertidae). Issue 3 (14th February 2020) - Giovannotti, Massimo; S'Khifa, Abderrahim; Nisi Cerioni, Paola; Splendiani, Andrea; Slimani, Tahar; Fioravanti, Tatiana; Olmo, Ettore; Caputo Barucchi, Vincenzo
Abstract: Two satellite DNAs (satDNAs) have been isolated and characterized from three populations of Atlantolacerta andreanskyi . One satDNA (AAN‐TaqI) has been isolated here from the first time. It is characterized by a tendency to AT enrichment (AT = 54.2%) and monomer length ranging from 187 to 199 bp. FISH experiments showed that this element occurs in subterminal position on the short arms of all chromosomes of the complement. The analyses of genetic variability of AAN‐TaqI showed that the concerted evolution is acting effectively on these repeats that form separate clusters consistent with the geographic origin in the phylogenetic tree, thus supporting the hypothesis that A . andreanskyi would be a species complex. In addition, in the population from Jbel Aoulime this satDNA is already differentiated into two subfamilies. The other satDNA belongs to the family of IMO‐TaqI already isolated in other lacertids. Differently from AAN‐TaqI, concerted evolution does not seem to act effectively on this element that is not differentiated between populations. These results confirm that IMO‐TaqI (AT = 53.4%) is conserved in both chromosomal position and most of its sequence in the lacertids from which it has been characterized so far. Its remarkable evolutionary conservation for about 45 million years could indicate that this satDNA may have a functional role that future investigations could unveil. Once again, this study shows how satDNAs coexisting in the same genome may differ in their evolutionary pattern, even though the reasons underlying this phenomenon in the species here studied have still to be fully understood. Abstract : In this study, two satellite DNAs (satDNAs) were isolated and characterized in three populations of the Atlas dwarf lizard, Atlantolacerta andreanskyi : AAN‐TaqI and IMO‐TaqI. AAN‐TaqI is a pericentromeric satDNA and has been described here for the first time. It occurs in subterminal position on the short arms of all chromosomes of the diploid complement of this species and, in the phylogenetic tree, its repeats cluster according to the population of origin. IMO‐TaqI belongs to the same family as the satDNA previously isolated in several species of Lacertidae. This repetitive element shows a certain degree of conservation in both chromosomal position and nucleotide sequence despite 45 million years of evolutionary history, thus suggesting an important functional role for this element. FISH with AAN‐TaqI fluorescent probe (red signal) onto metaphases from female (a) and male (b) of A. andreanskyi . FISH with IMO‐TaqI fluorescent probe (red signal) onto metaphases from female (c) and male (d) of A. andreanskyi . Arrow indicates the W chromosome. Scale bars = 10 µm. Research Highlights: Two satDNAs have been described in Atlantolacerta andreanskyi . AAN‐TaqI has been described here for the first time, whereas IMO‐TaqI had been already described in other species of lacertids and it is evolutionary conserved in these lizards.